1992
DOI: 10.1111/j.1600-0722.1992.tb01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweets and other sugary products tend to be the primary etiologic factors in dental caries

Abstract: The aim of this study was to analyze the relationships between caries incidence and each of seven caries‐related factors in a group of 15‐ to 18‐yr‐olds as well as in single and combined subgroups representing favorable or less favorable fractions of six of the factors. Sixty‐nine 18‐yr‐olds were interviewed about consumption of sweets and other sugar‐containing products during the past 3 yr and examined for oral hygiene, salivary counts of mulans streptococci and lactobacilli, salivary flow rate and oral suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
0
14
0
2
Order By: Relevance
“…There were 15 papers graded B1, reporting a total quantity of sucrose as measured in gm d −1 , one paper stated gm of sucrose consumed per 1000 kcal consumed (35), and one paper stated quantities of sucrose as large , moderate and small amounts (28). All other manuscripts did not assess total sugar consumption, and this was recorded in Table 3 as NA (not applicable).…”
Section: Discussionmentioning
confidence: 99%
“…There were 15 papers graded B1, reporting a total quantity of sucrose as measured in gm d −1 , one paper stated gm of sucrose consumed per 1000 kcal consumed (35), and one paper stated quantities of sucrose as large , moderate and small amounts (28). All other manuscripts did not assess total sugar consumption, and this was recorded in Table 3 as NA (not applicable).…”
Section: Discussionmentioning
confidence: 99%
“…The r value increased to 0.70 in children with poor cleanliness and considerable dental plaque and low salivary flow. They stated that the`¼ explanatory value of about 49%,¼ is remarkable and seems to be the highest value reported for any caries-etiologic factor in observational studies' 89 . The authors concluded that`¼ consumption of sweets should still be considered an important caries-related factor ¼' 89 .…”
Section: Relationship Between Frequency and Amount Of Sugar Intake Anmentioning
confidence: 98%
“…They stated that the`¼ explanatory value of about 49%,¼ is remarkable and seems to be the highest value reported for any caries-etiologic factor in observational studies' 89 . The authors concluded that`¼ consumption of sweets should still be considered an important caries-related factor ¼' 89 . Recent investigations in the Netherlands show a strong relation between the consumption of sweets and caries experience in school children 90 .…”
Section: Relationship Between Frequency and Amount Of Sugar Intake Anmentioning
confidence: 98%
“…In the presence of poor oral hygiene, the use of sugary products is extremely harmful for dental health, as shown among young adults in Sweden (19). In Finland, the nationwide survey in 1980 showed analogous findings among adults: the combination of frequent toothbrushing and limited use of sugar was associated with a lower occurrence of caries (20, 21), which may partly result from the beneficial topical effect of fluoride toothpaste.…”
mentioning
confidence: 99%